2006
DOI: 10.1093/rheumatology/kel071
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions for the treatment of acute and prevention of recurrent gout—a systematic review

Abstract: The shortage of robust data to inform the management of a common problem such as gout is surprising. All of the drugs used to treat gout can have serious side effects. The incidence of gout is highest in the elderly population. It is in this group, who are at a high risk of serious adverse events, that we are using drugs of known toxicity. The balance of risks and benefits for the drug treatment of gout needs to be reassessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 40 publications
0
55
0
1
Order By: Relevance
“…Moreover, all of the drugs used to treat gout can have serious side effects (58). In addition, evidence was recently provided that men with gout have an increased risk of death as the result of an elevated risk of cardiovascular diseases, particularly coronary heart diseases (59).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all of the drugs used to treat gout can have serious side effects (58). In addition, evidence was recently provided that men with gout have an increased risk of death as the result of an elevated risk of cardiovascular diseases, particularly coronary heart diseases (59).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, benzbromarone seems well tolerated in general use [5] in contrast to allopurinol, which causes frequently (2-5%) allergic skin reactions. The uncertainty remains whether the efficacy-safety balance of benzbromarone really is unfavourable, compared to the other antihyperuricemic drugs available like allopurinol, probenecid and sulphinpyrazone [6]. In Europe, benzbromarone was available only as a prescription uricosuric drug in a limited number of countries.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, theoretically, the urate balance, in terms of the ratio of overproduction and underexcretion of urate, may be clinically important for the rational choice of a uricostatic drug, a uricosuric drug or a combination of both. However, there are no trials to support or refute this theory [6]. From observational studies, it is concluded that benzbromarone 75-120 mg/day is very effective in the control of hyperuricemia, better than allopurinol 300-450 mg/day [5,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, each patient greatly benefits from low-purine diet, and its effects in some patients are comparable to those achieved via medical treatment. Moreover, altering eating habits is more cost-effective and safer than pharmacotherapy, due to elimination of any drug-related side effects, which is especially important in the elderly [14]. This does not mean that medical therapy should be relinquished altogether, yet rational planning of the daily menu increases the chance of dose reduction (including complete discontinuation) and eliminates a number of risk factors for the development of gout (e.g.…”
Section: Hyperuricemia and Diet -Epidemiological And Clinical Datamentioning
confidence: 99%